Ectopic Pregnancy after Bilateral Tubal Ligation in a Woman with Asymptomatic Fitz-Hugh-Curtis Syndrome - Aoun, Hakmi; Alhomsi, Sousan; Mousa, Mira; Al-Jefout, Moamar (Jordan Medical Journal, 2022)
This case report illustrates an incidental finding of asymptomatic Fitz-Hugh-Curtis syndrome in a 34-year old woman undergoing laparoscopy due to a spontaneous ruptured ectopic pregnancy after bilateral tubal ligation. To our knowledge, this is the first case that reported an atypical presentation in a twofold aspect: the presence of perihepatic adhesions associated with asymptomatic pelvic inflammatory disease (Fitz-Hugh-Curtis Syndrome) with a history of bilateral tubal ligation, and the spontaneous tubal ectopic pregnancy after a failed tubal ligation. This report highlights the clinical importance of conducting an attentive examination of the pelvis via surgical exploration of all abdominal cavity including perihepatic space, especially in women with suspected pelvic inflammatory disease and ectopic pregnancy.